Survey of Native American Literature - Dickinson, Joshua (SUNY Press, 2018)
Survey of Native American Literature offers a multi-genre approach to the field of Native American literature. Each section contains several representative voices, with more recent writings linked and older ones included either in full or as excerpts. Texts are organized with major sections on creation myths, fiction, poetry, and nonfiction/memoir. Standing Bear's Land of the Spotted Eagle is included, along with a scattering of non-Native writers for contrast. The text also focuses on experiencing Native literature through Western lenses, since that is the viewpoint through which students necessarily approach the topic. This survey textbook overviews Native American literature from its origins in poems and creation myths of the continent's hundreds of Native cultures. Texts are organized with major sections on creation myths, fiction, poetry, and nonfiction/memoir. Standing Bear's Land of the Spotted Eagle is included, along with a scattering of non-Native writers for contrast. The text also focuses on experiencing Native literature through Western lenses, since that is the viewpoint through which students necessarily approach the topic. The text adapts Lumen Learning's Introduction to Literature course shell, which operates with a CC-BY license and was provided by Ivy Tech Community College. Most of the texts are available through web or PDF links. The basic Introduction to Literature material is mostly hidden from student views, but is kept in case instructors wish to use it. Lumen Learning, Jefferson Community College, SUNY https://courses.lumenlearning.com/suny-jeffersoncc-nativeamericanlit/